Biopsychosocial experiences of elite athletes retiring from sport for career-ending injuries: a critically appraised topic - Moore, H. S.; Walton, S. R.; Eckenrod, M. R.; Kossman, M. K. (Journal of Sport Rehabilitation, 2022)
Clinical Scenario: Injuries cause individuals varying amounts of time loss from participation, which may depend on injury and sport-specific factors such as level of participation. Athletes who never return to sport either choose or are forced to retire due to numerous factors. At elite levels of play, when an athlete chooses retirement, they have the opportunity to create and execute a retirement plan; however, if unexpected (eg,due to career-ending injury), athletes may struggle to transition out of sport effectively, impacting physical, mental, and social health. The biopsychosocial model looks at the relationship between biology, psychology, and socio-environmental factors. Therefore, the purpose of this study was to better understand the biopsychosocial experiences elite athletes face after a career-ending injury so that sport stakeholders can develop and implement strategies to support a healthy transition. Clinical Question: How does suffering a career-ending injury affect elite athletes` biopsychosocial experiences during retirement from sport? Summary of Key Findings: All studies found that a career-ending injury negatively impacted athlete`s biopsychosocial health during the transition period. In addition, social support was identified as a positive coping mechanism and research highlighted the role of education in promoting successful transitions. Sport stakeholders should educate athletes regarding the importance of creating secondary plans. By creating a culture of athletic and nonathletic identity, athletes can feel empowered to navigate different phases of their life despite transition being forced upon them due to injury. Clinical Bottom Line: Career-ending injuries negatively impact the biopsychosocial experiences of elite athletes as they transition out of sport. Athletes may face many transitional challenges including a loss of identity, a lack of external support, and/or mental health decline; those more closely identifying with their role as an athlete tend to have a harder transition. Therefore, it is important for all athletes to be adequately prepared for sport retirement, especially given the uncertainty about when and how retirement may occur. Strength of Recommendation: Collectively, the body of evidence included to answer the clinical question aligns with the strength of recommendation of C.